Development of 3dimensional Diorama in The Natural Science Learning Especially Lesson of Ekosistem for Grade V Students - Prabowo, Desi Wulandari, Dady Mukti (Universitas Negeri Semarang, 2018)
Sains education is the one of lesson that must be given for student of elementary school, but in fact, Sains education still unoptimally done. Based on datas of observation, interview, and document that be found at Kalibanteng Kidul 02 Semarang State Elementary School is showed information that there is problem with the relevance learning media is still low. So, need to be developed 3 dimension diorama media in sains education. The purpose of this research is to describe the steps of developing 3 dimesion diorama media, to know about validity of 3 dimension diorama media, and to know about efectivity of 3 dimension diorama media in the learning. Type rsearch is Research and Development (R&D) with some step are pra research, collecting data, preparing the media design, product validation, product reparation, small scale test, big scale test, and the last product. Research population is all student of grade V at Kalibanteng Kidul 02 Semarang State Elementary School. Research sample is student f grade V with jenuh sample technic. Collecting datas technic are observation, interview, test, angket, and documentation. Analyzing data technic use analyzing product data, analyzing first data/normality test, T test, and N-Gain test. The result of the research shows that 3 dimension diorama media can be used in sains educational learning with the value percentage from media specialist is 94%, content specialist is 97%, media practicy is 97%, and content practicy is 93% with Ttest result is T -assesment (7,396) is bigger than T-table (1,671) and N -Gain test result is 0,7063 with high criteria. This research conclusion is effectivally be used in sains educational learning toward student learning result. Instruction for the next research can use 3 dimension diorama media in other lesson by adapted with component and design is related with the content that be teach.